A GESTÃO DE PESSOAS NO SETOR PRIVADO: A VISÃO SEGUNDO CRITÉRIOS DE EXCELÊNCIA DO PNQ, SUA CONTRIBUIÇÃO PARA O SUCESSO EMPRESARIAL E A PLENA SATISFAÇÃO DO CLIENTE. - Ribeiro, José Antonio Athayde (2004)
The approach to Personnel Management is broad and intense due to its importance in overall management. During the last century, Personnel Management underwent a rapid evolution as a consequence of both industrial growth and the influence of Behaviour scientists. The development of several practices as well as concepts presently used at work enviroment differ from those practiced in the beginning of the 19th century. In this work, Personnel Management is examined according to PNQ's principles, which is considered an model of excelence for managerial activities either in large as well as in small private companies. After presenting and discussing relevant aspects, it has been concluded that the PNQ model does estimulate Directors and Collaborators in reaching goals and objectives, in improving performance and productivity, in building a favorable organizational environment and, therefore, in achieving good results for customers.